2021
DOI: 10.35877/454ri.asci150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of mental distress during COVID-19 outbreak in Bangladesh: evidence from an online survey

Abstract: Novel Coronavirus disease 2019 (COVID-19) is an ongoing pandemic and life-threatening highly infectious disease outbreak. The people of Bangladesh are at high risk of COVID-19 and have already experienced various socio-economic, Physical health, and psychological consequences. Particularly, mental health problems are dominantly reported in the literature and should be controlled. The main objective of this epidemiological study is to assess the mental distress and identify its determinants using an online-base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Which condition may lead to quality of life in the environmental health domain (Lercher, 2003;Wong et al, 2018). A study conducted by Saha and Khan (2020), found that the majority of the respondents stated that staying at home is one of the best prevention techniques to avoid COVID-19. Most of the respondents were come from the urban area, had a university background, and had more information about COVID-19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Which condition may lead to quality of life in the environmental health domain (Lercher, 2003;Wong et al, 2018). A study conducted by Saha and Khan (2020), found that the majority of the respondents stated that staying at home is one of the best prevention techniques to avoid COVID-19. Most of the respondents were come from the urban area, had a university background, and had more information about COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the respondents were come from the urban area, had a university background, and had more information about COVID-19. Therefore they preferred to stay at home during the COVID-19 lockdown (Saha & Khan, 2020). Urban people with higher education levels have a higher chance getting updated information about COVID-19.…”
Section: Methodsmentioning
confidence: 99%